Adopsi E-Commerce Memediasi Hubungan Kesiapan Teknologi, Lingkungan Eksternal dan Literasi Keuangan Terhadap Kinerja Keuangan UMKM - Maghfiroh, Lailatul; Biduri, Sarwenda (E-Jurnal Akuntansi, 2022)
This study aims to determine whether the variable adoption of e-commerce is able to mediate the relationship between technological readiness, external environment and financial literacy on the financial performance of MSMEs with a study on MSMEs in Sidoarjo Regency. The research population for implementing SMEs in the food and beverage sector in Sidoarjo Regency. The sampling technique used the slovin formula, so that the sample obtained was 125 respondents of MSME actors. The data analysis technique used SmartPLS version 3.0 software. The results showed that technology readiness and financial literacy had no effect on the financial performance of MSMEs. However, external environmental variables affect the financial performance of SMEs. The adoption of e-commerce has an effect on financial performance. The adoption of e-commerce does not mediate the effect of technology readiness on the financial performance of MSMEs. However, the adoption of e-commerce can mediate the influence of the external environment and financial literacy on the financial performance of MSMEs. Keywords: E-Commerce Adoption; Technology Readiness; External Environment; Financial Literacy; MSME Performance